Assessing the value of loyalty scheme communications to British FMCG retailers' brands - MCLUNDIE, MICHAEL (2013)
Loyalty schemes are a key feature of many British FMCG retailers' marketing communications strategies, but there is no research on how communications language of these schemes can positively or negatively affect consumer perceptions of a brand. This study introduces the possibility of using a framework to assess 'unbranded' loyalty scheme communications and compare consumer perceptions with those of the retailer's brand. This framework was distributed to consumers as a survey, and it was found that some retailers' communications mirrored the perceptions of their brand, whilst others were relatively misaligned. This ultimately was likely to lead to a corresponding change in brand equity and showed how such a framework could be used to alter the way text was written, thus adding value to a brand.